Robust H[infinity] control of spacecraft rendezvous on elliptical orbit - Gao, X.; Teo, Kok Lay; Duan, G. (Elsevier Science, 2012)
This paper investigates the robust H∞H∞ control problem of spacecraft rendezvous on elliptical orbit. Based on Lyapunov theory, a sufficient condition for the existence of the robust H∞H∞ controller is given in terms of the periodic Riccati differential equation (RDE). Then, a stabilizable controller design method based on a fast multi-shot algorithm is proposed. With the controller obtained, the spacecraft rendezvous mission can be accomplished. An illustrative example is provided to show the effectiveness of the proposed control design method.